Leisure meets health: important intersections and alternative discourses. Issue 3 (27th May 2021) - Young, Janette; Maxwell, Hazel; Peel, Nicole
ABSTRACT: While it is generally accepted in the leisure field that leisure has a role, and arguably a key one in wellness and wellbeing, this is largely at odds with the operations and funding frameworks of contemporary healthcare systems. Governments spend much less on leisure which involves social aspects of health than they do on healthcare systems which are focussed on biomedical interventions. Yet, many leisure and healthcare practitioners and academics are aware of the intersections between leisure, health and wellbeing and the aim of this edition was to offer a forum for overtly presenting these intersections. Here we set the scene for the papers in this special edition, summarizing the contribution of each paper to progressing discussions regarding the intersections of leisure and health and suggesting future directions for exploration.